Metodika otsenki spetsial'noi fizicheskoi podgotovlennosti akrobatok-prygunii vysokoi kvalifikatsii - Kobzar, L. V.; Pilyuk, N. N. (Teorija i Praktika fiziceskoj Kul'tury, 1997)
The purpose of this study was to foundate the method of the special physical preparadeness's evaluation in the elite women-athletes specializing on acrobat jumps. 11 women-acrobat-jumpers of the higher qualification acted as subjects of this research. The results of the study had allowed to offer the method of women-acrobats-jumpers' special physical preparation. The experimental examination had demonstrated, that with a help of this method the effective direction by the women athletes' training can be realized and that the reach of the model characteristics ensures their readiness to competitional exercises' performing.